2014
DOI: 10.2337/dc14-2159
|View full text |Cite
|
Sign up to set email alerts
|

Mild Gestational Diabetes Mellitus and Long-Term Child Health

Abstract: OBJECTIVETo evaluate whether treatment of mild gestational diabetes mellitus (GDM) confers sustained offspring health benefits, including a lower frequency of obesity.RESEARCH DESIGN AND METHODSFollow-up study of children (ages 5–10) of women enrolled in a multicenter trial of treatment versus no treatment of mild GDM. Height, weight, blood pressure, waist circumference, fasting glucose, fasting insulin, triglycerides, and HDL cholesterol were measured.RESULTSFive hundred of 905 eligible offspring (55%) were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
138
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(154 citation statements)
references
References 33 publications
6
138
0
2
Order By: Relevance
“…Thus, the findings here align with previous results showing a high risk of macrosomia and later obesity among children born of mothers with gestational diabetes. 28,29 We further show that infants of mothers with diabetes are markedly larger during the first 24 months. Continued research is needed in other cohorts to verify the findings here given that others have shown that whereas children of mothers with diabetes are heavier, these patterns are not observed during infancy.…”
Section: Resultsmentioning
confidence: 80%
“…Thus, the findings here align with previous results showing a high risk of macrosomia and later obesity among children born of mothers with gestational diabetes. 28,29 We further show that infants of mothers with diabetes are markedly larger during the first 24 months. Continued research is needed in other cohorts to verify the findings here given that others have shown that whereas children of mothers with diabetes are heavier, these patterns are not observed during infancy.…”
Section: Resultsmentioning
confidence: 80%
“…41 This metabolic dysfunction could be induced by a prenatal exposure to intrauterine insults during critical periods of epigenetic programming, which could increase the risk for cardiovascular complications later in life. 21,22,43 Although our study added evidence supporting the implication of epigenetic modifications in the fetal metabolic programming of weight at birth and in mid-childhood, the impact on later life health and diseases, such as lipid metabolism impairments (according to the DOHaD hypothesis), needs to be studied. Nonetheless, it has been shown that metabolic dysfunctions later in life are predicted by birth weight and growth in childhood, for which placental LPL DNAm deregulation might be one of the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 86%
“…[20][21][22] Mothers from our cohort were carefully followed up, and those with GDM were treated in accordance with established clinical practices. Accordingly, GDM mothers gained significantly less weight in the last trimester of pregnancy as compared with NGT mothers, suggesting that they were compliant to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In one follow-up study, maternal depression rates 3 months after delivery were lower in the intervention group than in the group of mothers who received usual care [15]. Though the intensive treatment of mothers with GDM was associated with a significant decrease in birthweight and macrosomia, it was not found to result in a change in the child's BMI at age 4-5 [20] or in a reduction of childhood obesity or metabolic dysfunction at age 5-10 [21] in the follow-ups of the previously mentioned studies. Hence, longer follow-up studies are merited.…”
Section: Is Gdm Worth Treating?mentioning
confidence: 96%